The relationship between the spiritual well-being of university students in Hong Kong and their academic performance - Pong, Hok-Ko (International journal of children's spirituality, 2017)
The study aims to examine the relationship between the spiritual well-being of university students in Hong Kong and their academic performance measured by Cumulative Grade-Point Average, using both quantitative and qualitative methods. The quantitative part of the study consists of 1130 Year 2 and Year 3 students from three universities in Hong Kong. The questionnaire is adapted from the Spiritual Health and Life-Orientation Measure developed by John Fisher. Results indicate a moderately positive relationship between the spiritual well-being of the respondents and their academic performance. The qualitative part of the study is comprised of 11 focus group discussions. The findings of this support the quantitative findings and contribute to the exploration of how students' spiritual well-being and their pursuits of academic success are correlated. The several spiritual attributes, namely, concentration, persistence, self-confidence, self-discipline and interpersonal relationships are found in the resulting positive relationship through the qualitative findings.